Treatment Outcome of 22 Dogs With Masticatory Muscle Myositis (1999-2015). (December 2018) - Castejon-Gonzalez, Ana C.; Soltero-Rivera, Maria; Brown, Dorothy C.; Reiter, Alexander M.
Medical records of dogs diagnosed with masticatory muscle myositis (MMM) at Ryan Veterinary Hospital of the University of Pennsylvania during a period of 17 years (from 1999 to 2015) were reviewed. Twenty-two dogs were included in this retrospective case series study. Immunosuppressive doses of prednisone were prescribed to all dogs. Twenty dogs had full recovery of masticatory function. The mean (SD) improvement in the vertical mandibular range of motion (vmROM) was 5.3 (3.1) cm during the first 4 weeks of treatment (weeks 1-4) and 2.8 (2.2) cm during the subsequent 8 weeks (weeks 5-12). The vmROM continued to improve for several more months. Six dogs had a relapse, but the clinical signs were more severe in dogs when no longer receiving prednisone compared to dogs still on prednisone at the time of relapse. When diagnosed and treated appropriately, MMM has a good prognosis with relatively quick return to masticatory function. Early discontinuation of prednisone therapy should be avoided. Approximately 1 year of therapy is recommended prior to discontinuing the medication. Educating the client about how to perform muscle palpation, determine vmROM at home, recognize signs of pain, and notice behavioral changes may help in the early detection of relapses.